High-temperature oxidation of superalloy C-263 of rings for aircraft engines - Gaona Tiburcio, Citlalli; Lira Martínez, Manuel Alejandro; Taboada Solís, Jorge Manuel; Zambrano Robledo, Patricia del Carmen; Estupiñan López, Francisco Humberto; Cabral Miramontes, José Ángel; Almeraya Calderón, Facundo (InTech, 2018)
The present investigation was conducted to study the oxidation kinetics of nickel-based superalloy 263, used in the manufacture of rings for aircraft engines. For carrying out this study, we first conducted microstructural characterization of the pieces using the techniques of optical microscopy, scanning electronic microscopy, and X-ray diffraction. Subsequently, using the thermogravimetric analysis, the kinetic oxidation of the metal was performed in a temperature range between 700 and 1000°C, using atmospheres of O2. The results of the micrographs show the formation of a protective oxide film on the surface of the material in different oxidizing agents. Finally, it was found that the kinetics of high-temperature oxidation of the superalloy C-263 obeys the parabolic rate law.